Suicidal risk in patients with aggression in schizophrenia: a systematic review - Lidia Bravve; Maria Kaydan; Georgy Kostyuk; Georgy Kostyuk; Georgy Kostyuk; Georgy Kostyuk (Frontiers in Psychiatry)
IntroductionSuicide represents the primary risk factor for mortality among individuals diagnosed with schizophrenia, with a mortality rate that is 10 times higher than that observed in the general population. In the study of individuals who have committed suicide, some exhibited a high risk of aggression and impulsivity, which permitted the consideration of these indicators as predictors of suicide risk. The extant literature contains a number of debates concerning diverse conceptualizations of aggression and impulsivity in the context of suicidal behavior. The present study examined the levels of verbal and physical aggression in individuals diagnosed with schizophrenia, finding that 43% exhibited verbal aggression and 24% physical aggression, levels that are significantly higher than those observed in the general population. Concurrently, an analysis of the psycho-emotional state of patients with suicidal behavior in the anamnesis reveals an indication that the suppression of emotions (including aggression) and the avoidance of harm may result in suicide. This finding is at odds with the previously mentioned results, and consequently, the present review sought to assess the impact of aggressive behavior on suicide risk in patients diagnosed with schizophrenia.MethodsThe search was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The literature search was conducted in PubMed, Cochrane Library, PsychINFO and Mendeley Data. The search terms used were “aggress*” and “suicid*” or “autoaggress*” and “schizophrenia*”. The search was limited to papers published between 2009 and 2024 (the last 15 years), and the search was continued until November 2024. This systematic review has been registered in PROSPERO (CRD42024628033).ResultsA total of 1,364 articles were identified, 295 of which were duplicates. Following a thorough review, 1,046 articles that did not align with the title and abstract were excluded from the analysis. During the literature search, 23 articles were read in full, of which eight studies met the inclusion criteria. A total of eight studies provided information on the effect of aggressive behavior on suicide in patients with schizophrenia. Of these, six studies demonstrated a positive association between aggression and suicidal behavior or employed a logistic regression model in which the risk of aggression increased the risk of suicide and vice versa. Conversely, two studies revealed no association between suicide risk and aggression.ConclusionsPatients with a documented history of suicide attempts and aggressive behavior are considered to be at risk of suicide, thus emphasizing the necessity for preventive measures to be implemented for this cohort of patients. However, the conclusion regarding the influence of aggressive behavior on increased suicide risk may not be entirely accurate and may not reflect the true extent of the problem, due to the significant number of methodological inaccuracies and discrepancies in the design of the studies included in the review.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024628033, identifier CRD42024628033.